KUALITAS AIR SUMUR GALI DITINJAU DARI KONDISI LINGKUNGAN FISIK DAN PERILAKU MASYARAKAT DI WILAYAH PUSKESMAS I DENPASAR SELATAN - Ni Made Marwati; N.K. Mardani; I Ketut Sundra (Master Program of Environmental Science, Postgraduate Program of Udayana University)
water quality reduction potentially happen. Anxiously wells water quality reduction will happen in consequences frombad sanitation, like household waste water seepage, chemistries cesspool, laundry, etc.This research applied comparatively descriptive characteristic approach quantitative method. Well water wassample taken from 9 units on February and 9 units on April 2008. Sample unit was taken by purposive sampling methodfor excavated wells and random sampling method for water sample. Analysis result for well water was compared withquality standard of Bali Governor regulation No.8 ‘2007 and with quality standard of Health Minister RepublicIndonesian Rule No.907 ‘2002 and also pollution index according to Minister of Alive Environment Decision No.115‘2003. Water quality was calculated based on pollution index correlated with physical environment condition withSpearmen test (Rho) and measuring society behaviour by Sturges.Research result shows that in February for parameter BOD, Fe and total coliform slightly exceeded water qualitystandard and in April 2008 for parameter DO, BOD, Fe and total coliform slightly exceeded water quality standard class Iand drinking water quality standard. Pollution Index (IP) with result for all well water researched is under 5 (five) that is(1 < IP ? 5) including low pollution. By using Spearmen analysis, so that alternative hypothesis unaccepted, well physicalenvironment condition (IS) not in correlated to excavated wells water standard quality with Rho ( ? ) 0,147 andsignificance 0,705 more than ? 5 %. Interview result shows that 9, 10 % respondents have good behaviour and 90, 9 %respondents have understanding behaviour in maintaining clean water resource managed.Suggested to local government of Denpasar city this related to clean water (PDAM) to improve distribution ofclean water so that can fulfil 100% clean water necessity of the city. Particularly to Public Health Centre I SouthDenpasar is expected to conducting chlorinization regularly to public. Society is expected to improve well physicalenvironment condition and increases healthy life behaviour.